2011
DOI: 10.1017/s1743921312010940
|View full text |Cite
|
Sign up to set email alerts
|

Are planetary nebulae derived from multiple evolutionary scenarios?

Abstract: Abstract. Our understanding of planetary nebulae has been significantly enhanced as a result of several recent large surveys (Parker et al., these proceedings). These new discoveries suggest that the 'PN phenomenon' is in fact more heterogeneous than previously envisaged. Even after the careful elimination of mimics from Galactic PN catalogues, there remains a surprising diversity in the population of PNe and especially their central stars. Indeed, several evolutionary scenarios are implicated in the formation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…They further suggest that in a several months long outburst a main-sequence companion accretes mass from an AGB star and launches jets, that both shape the bipolar PN and powered an ILOT event. The ILOT scenario was mentioned in relation to more PNe (Frew & Parker 2012;Boumis & Meaburn 2013;Clyne et al 2014;Frew et al 2016). Corradi et al (2014a) raise the possibility that the YSO bipolar nebula Ou4 was formed in an ILOT event, as Boumis & Meaburn (2013) suggest for the PN KjPn 8 that has a similar morphology.…”
Section: Intermediate-luminosity Optical Transients (Ilots)mentioning
confidence: 99%
“…They further suggest that in a several months long outburst a main-sequence companion accretes mass from an AGB star and launches jets, that both shape the bipolar PN and powered an ILOT event. The ILOT scenario was mentioned in relation to more PNe (Frew & Parker 2012;Boumis & Meaburn 2013;Clyne et al 2014;Frew et al 2016). Corradi et al (2014a) raise the possibility that the YSO bipolar nebula Ou4 was formed in an ILOT event, as Boumis & Meaburn (2013) suggest for the PN KjPn 8 that has a similar morphology.…”
Section: Intermediate-luminosity Optical Transients (Ilots)mentioning
confidence: 99%
“…From the IRAS two-colour diagram, they find that WELS are shifted to bluer colours than the other [WR] PNe. Frew & Parker (2012) show that WELS have larger scale height compared to other many CS classes and consequently they rise from low mass progenitor stars.…”
Section: Introductionmentioning
confidence: 89%
“…These lines are indistinguishable in width from the nebular lines, although on low dispersion spectra the group of lines around 4650Å and the C IV doublet around 5805Å may appear to be broad features. Frew & Parker (2012) noted that the characteristics WELS recombination lines such as C IIII, C IIV and N IIII were also observed in some massive O-type stars, as well as in low-mass X-ray binaries and cataclysmic variables. Corradi et al (2011) observed these C IIII, C IIV and N IIII emission lines in the spectrum of the close binary CS of the high-excited PN IPHASX J194359.5+170901.…”
Section: Introductionmentioning
confidence: 97%
“…This, and their use as key Galactic probes, provides strong motivation to hunt for them. Much progress has been made since the major Galactic PNe discoveries report by Parker et al (2006) and Miszalski et al (2008), as well as obtaining a better understanding of the different evolutionary pathways that can lead to PNe formation, e.g., Stanghellini and Pasquali, (1995) and Frew and Parker (2012).…”
Section: Basic Pne Propertiesmentioning
confidence: 99%